PRINSIP BANKRUPTCY REMOTE DALAM SEKURITISASI ROYALTI HAK CIPTA - Stefani Kaonang (Universitas Airlangga, 2015)
Nowadays everyone needs source of funding to expand their business in every field. One way to get funding sources is from securities. Form of securitization always experience growth in several countries in various fields including intellectual property right, especially copyright. Every copyright holder can continue to help creators to always work through the securitization process. Securitization in copyright conducted through a vehicle called Special Purpose Vehicle or Special Purpose Entities as an issuer of securities. The securities acquired from commercial agreement/license agreement between the third party and the holder of the copyright in the form of royalties. These royalties which are released to the market in the form of securities. This gives rise to the right to collect for securities holder investors to a Special Purpose Vehicle or Special Purpose Entities. This collection right which can result in the implementation of bankruptcy law to a Special Purpose Vehicle or Special Purpose Entities are. However, the Special Purpose Vehicle or Special Purpose Entities can not be bankrupted just because the inside of a Special Purpose Vehicle or Special Purpose Entities contain bankruptcy remote principle therein.